PENGARUH CURRENT RATIO,NET PROFIT MARGIN DAN ECONOMIC VALUE ADDED TERHADAP HARGA SAHAM PADA PT.CHAMPION PACIFIC INDONESIA TBK - Dede Pramurza (Gapenas Publisher, 2022)
This Study aims to determine how much influence the Current Ratio, Net Profit Margin, and Economic Value Added on the Stock Prices at PT. Champion Pacific Indonesia Tbk. 2011-2020 period. The analytical method used in this research is descriptive quantitative using Multiple Linear Regression Analysis. Based on the results of the study indicate the Current Ratio, Net Profit Margin, and Economic Value Added do not have a significant on the Stock Prices at PT. Champion Pacific Indonesia Tbk. 2011-2020 period, both simultaneously and partially. This is because tcount is smaller than ttable and fcountis smaller than ftable